Adhesion of Cercaria (Larva of Helminth Parasites) to Host by Lectins- Carbohydrates Bonds as a Model for Evaluation of Schistosoma Entrance Mechanisms in Cercarial Dermatitis - A Farahnak; N Dabagh (Tehran University of Medical Sciences, 2008)
Background: Cercariae (larva of helminth parasites) are covered by a thick glycocalyx coat, which serves as an osmotic protection during their free existence, and contain carbohydrates conjugated as glycoproteins, glycolipids and mucopolysaccharides. Although, limited studies have been made on life cycle of cercariae from fresh water snails, however, carbohydrate studies on cercariae have not been done in Iran so far. This study was made to determine the cercariae specifications from Lymnaea gedrosiana and evaluation of surface carbohydrates as receptors for host lectins in a host-parasite relationship system as a model in human schistosomiasis including cercarial dermatitis in Khuzestan Province. Methods: For this purpose, snails were collected from Dezful region in Khuzestan Province and cercariae were obtained by shedding method and identified by valuable keys. Experimental infection was established in the Culex pipiens (Culicidae mosquitoes) larvae for further identification and mode of adhesion. To detect the mode of adhesion, surface carbohydrates of cercariae were detected by lentil (Lens culinaris) lectins. Results: Examined snails were infected with xiphidiocerceria of trematodes and metacercariae were obtained from Culex pipiens. Also, Mannose monosaccharides- CH2OH (CHOH) 4CHO - were detected particularly on the glands of cercariae. Conclusion: Adhesion of cercariae to their host by lectins-carbohydrates bonds is the first stage of host-parasite relationship. This phenomenon could be happened for animal schistosome's cercaria in cercarial dermatitis.